Skills Development through Virtual Art-Based Learning: Learning Outcomes of an Advanced Training Program for Project Managers - Berit Sandberg; Elena Stasewitsch; Jochen Prümper (Education Sciences, 2022)
With regard to emerging requirements of the professional field, uncertainty competence is a skill to be cultivated and integrated into project management education and training. Art-based learning seems to be a promising approach because the artistic mindset is a suitable model for coping with uncertainty. However, it is widely unclear to what extent art-based learning’s experiential nature will result in soft skills development under the restrictions of distance education. The present quantitative study explores whether—in a virtual learning environment—art-based executive training has a measurable effect on uncertainty competence. Data collection and analysis applied a quasi-experimental pretest-posttest control group design. Participants in the experimental group completed a month-long virtual training program based on visual arts. Contrary to its objective, the program did not cause meaningful changes in uncertainty competence or perceived stress but had a significant effect on participants’ attentiveness and presence. Participants achieved a higher level of mindfulness in dealing with complexity. The results imply that—even in virtual settings—art-based approaches enhance perceptive capacity and social presence but need to be long-term, related to participants’ individual work-context, and disturb participants’ routines to have an effect on uncertainty competence.